CARTILAGINOUS MATRIX COMPONENTS PRODUCTION IN THE IN VIVO â€˜CELL-SCAFFOLDâ€™ CONSTRUCT - Noorhidayah Md Nazir; Zulkifly, Ahmad Hafiz; Khalid, Kamarul Ariffin; Zainol, Ismail; Zamli, Zaitunnatakhin (International Journal of Allied Health Sciences, 2019)
Articular cartilage has the potential to be regenerated via tissue engineering strategy. This approach aims to improve the available cartilage degenerative related treatment modalities. With the utilisation of the tissue engineering principles, the engineered cartilage tissue was formed in the in vitro three-dimensional (3D) culture and evaluated in the in vivo ectopic implantation setting. The cultured chondrocytes at passage-1 were transfected with SRY (Sex Determining Region Y)-box9 (SOX9) and Telomerase Reverse Transcriptase (TERT) genes. The cells were grouped into 1) SOX9/TERT-transfected chondrocytes, and 2) non-transfected chondrocytes (NTC). The NTC serves as a control. A total of 1Ã—105 cells were seeded into the porous poly(lactic-co-glycolic) acid (PLGA) with and without fibrin scaffolds. The formed in vitro â€œcell-scaffoldâ€ construct were cultured for three weeks. The constructs were subcutaneously implanted at the dorsum of the athymic mice for two and four weeks. The evaluation includes macroscopic observation as well as histological analyses to detect sulphated glycosaminoglycan (sGAG) and proteoglycan productions. The in vivo constructâ€™s morphology has the appearance that resembles cartilage. Regardless of cells and scaffold groups, the in vivo constructs at week-4 were firmer than the constructs at week-2 confirmed thru simple palpation using forceps. The constructâ€™s rigidity supported by the extracellular matrix distribution in the construct. The presence of sGAG can be visualised in all in vivo constructs. However, the proteoglycan can be seen only at the pericellular matrix region of the week-4 SOX9/TERT-PLGA/fibrin construct. The presence of these two extracellular matrix components indicates ongoing cartilaginous tissue development. The overall findings showed that the SOX9/TERT-PLGA/fibrin construct has the potential to be developed into functional cartilage tissue. The information retrieved from this study gives some insight into the translational endeavours to manoeuvring laboratory-grown engineered tissues to tangible impact in the future clinical application.